Open Source Software and Proprietary Software for Library Automation - Mamoriya, Alka (Journal of Advanced Research in Library and Information Science; Vol 8 No 2 (2021): Journal of Advanced Research in Library and Information Science, 2021)
By using library automation software the work gets done easily and quickly. There is no error in library housekeeping operation and solve many issues like stock verification, bibliography, OPAC search operation easily by library automation software. Open-source software is Open bibliog. library management software, KOHA, Avanti. Proprietary software is e-Granthalaya, SOUL, TLSS, and Libsys. By using any software handling library housekeeping and administrative work is very easy and reduces duplication. Many modules are available in software for library operation and each has its unique quality by which the work can be done easily. How to cite this article:  Mamoriya A. Open-Source Software and Proprietary Software for Library Automation. J Adv Res Lib Inform Sci 2021; 8(2): 1-3. DOI: https://doi.org/10.24321/2395.2288.202101